Neurogenic inflammation and sensitivity to environmental chemicals. - Meggs, William J. (East Carolina University, 1993)
Neurogenic inflammation as a pathway distinct from antigen-driven, immune-mediated inflammation may play a pivotal role in understanding a broad class of environmental health problems resulting from chemical exposures. Recent progress in understanding the mediators, triggers, and regulation of neurogenic inflammation is reviewed. Evidence for and speculations about a role for neurogenic inflammation in established disorders such as asthma, rhinitis, contact dermatitis, migraine headache, and rheumatoid arthritis are presented. The sick building syndrome and multiple chemical sensitivity syndrome have been defined as clinical entities in which exposure to chemical inhalants gives rise to disease. Current data on the existence of chemical irritant receptors in the airway and skin are discussed; neurogenic inflammation arising from stimulation of chemical irritant receptors is a possible model to explain many of the aspects of chemical sensitivities. Originally published Environ Health Perspect, Vol. 101, No. 3, August 1993
Keywords: Asthma; Indoor air pollution; Multiple chemical sensitivity syndrome; Neurogenic inflammation; Neutral endopeptidase; Reactive airways dysfunction syndrome; Reactive upper airways dysfunction syndrome; Rhinitis; Substance p; Sick building syndrome